Epidemiology of children with acquired immune deficiency syndrome (stage 3): A referral hospital‐based study in Iran. Issue 1 (January 2016) - Movahedi, Zahra; Mahmoudi, Shima; Pourakbari, Babak; Keshavarz Valian, Nasrin; Sabouni, Farah; Ramezani, Amitis; Bahador, Abbas; Mamishi, Setareh
Abstract : Lack of recognition of human immunodeficiency virus (HIV) infection especially in children and delayed implementation of effective control programs makes HIV infection as a major cause for concern. Information on HIV epidemiology in Iran as well as other Islamic countries is limited. The aim of our study was to describe the clinical manifestation and laboratory finding of HIV infected children who were admitted to a referral Children Medical Center (CMC) in Tehran, Iran, during 11 years from January 2002 to January 2013. This was a retrospective study carried out over a period of 11 years. The records of all patients attending to the CMC with confirmed acquired immunodeficiency syndrome (AIDS) were screened. The patients were evaluated for social circumstance, family history, age, gender, clinical, and laboratory features. Clinical data including fever, respiratory distress, diarrhea, rash, etc. as well as laboratory tests including complete blood count, serum glucose level, electrolytes, liver function test, cultures, CD4 lymphocyte count were evaluated. During the study period, 32 HIV positive children were enrolled. The majority of patients were presented with weight loss, prolonged fever, respiratory infection and chronic diarrhea. In this study, salmonella infections as well as streptococcal pneumonia and candida infections followed by, tuberculosis and Pseudomonas aeruginosa infections were the predominant opportunistic infections. Since the number of HIV‐positive children has been alarmingly increasing in recent years and perinatal transmission is the most common route of HIV infection in children, essential recommendations for prenatal HIV testing as well as appropriate antiretroviral therapy by HIV infected mothers are needed. J. Med. Virol. 88:64–68, 2016 . © 2015 Wiley Periodicals, Inc.